Akselerasi Kemandirian Ekonomi Guru PPPK Paruh Waktu Melalui Strategi Digital Marketing Berbasis Local Networking Di Kecamatan Telaga - Rahmawati Sarizki Habie; Muhamad Ihsan Said Ahmad; Maghfirah Sari Aziz; Andi Zulitsnayarti Mardhani (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The economic welfare of Early Childhood Education (PAUD) and Kindergarten (TK) teachers holding Part-Time Government Employees with Work Agreements (PPPK) status in Telaga District remains a challenge requiring tactical solutions. Although many teachers already possess independent business units (MSMEs), such as culinary products, stationery, and furniture, their marketing effectiveness is still hindered by low digital literacy. This community service activity aims to enhance teachers' digital marketing competence through the Digital Teacherpreneurship concept. The implementation method employs the Participatory Action Learning (PAL) approach, encompassing problem recognition, digital platform transformation, and promotional network synergy phases. Data analysis was conducted using a descriptive qualitative technique through participatory observation. The results indicate an 85% increase in participants' digital understanding. Participants successfully configured digital storefronts using the WhatsApp Business Catalog feature and initiated collective cross-promotion strategies. This innovation proved effective in expanding market reach without additional costs, while simultaneously maintaining teachers' economic stability without compromising their professional integrity at school.